Optimizing Tourist Visits through Digital Tourism Socialization Campaign at Watubangga Beach Tourism Destination - fatma; Desi, Desi; Rezky, Rezky; Yusran, Yusran; Efendi, Iswar; Raihan, Ahmad; Putriani, Dian Rohma; Syaiful, Muhammad; Kartomo, Kartomo (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2024)
Tourism is a crucial economic sector in regional development, including Watubangga Beach, Southeast Sulawesi. Despite its significant potential, efforts to market and promote this destination have yet to be optimal in attracting tourists. This project aims to leverage digital technology to enhance the appeal of Watubangga Beach, aiming to provide substantial benefits to both the local community and visitors. Methods employed include field observations, interviews with tourism managers, establishment of social media accounts, mapping the location on Google Maps, providing entrance tickets and tourism brochures, coastal area cleanup, and installation of directional signage. This article discusses digital-based tourism promotion strategies to increase visitor numbers to Watubangga Beach. By maintaining cleanliness, utilizing social media, and actively involving tourists, it is hoped to create satisfying tourist experiences. The digital marketing strategies are expected to directly benefit tourism managers by boosting visitor numbers and advancing tourism at Watubangga Beach.